Symposium 11: Researching Theory Led Designs for e-Learning Communities and Collaborative Learning: Symposium Introduction - McConnell, David; Dirckinck-Holmfeld, Lone (Proceedings of the International Conference on Networked Learning, 2004)
This Symposium arises from the work of a Special Interest Group in the EU funded project “EQUEL” – equality in e-learning. The SIG worked together over one year on a variety of research issues concerned with “Theory led Designs for E-Learning Communities and Collaborative Learning”. The Symposium focuses on research into the design, implementation and sustainability of networked e[1]learning groups and communities. We draw on our experiences as practitioner researchers – people who are actively involved in the design and practice of networked e-learning and who carry out critical research into that practice – to present four critical case studies illustrating the divergent features of design which we are each implementing and researching, and the learning outcomes that are associated with each design. These designs all focus on networked e-learning communities of one kind or another in continuing education contexts, and include blended courses and fully virtual courses; short courses lasting up to 10 weeks, and longer courses (Masters) lasting up to two years.